(untitled) (Research, Society and Development, 2025)
This study addresses metabolic syndrome in rural communities environmentally exposed to pesticides in the Amazon, with an emphasis on sociodemographic and epidemiological profiles in the municipality of Belterra, in the state of Pará. The research is justified by the concern about cardiometabolic impacts on vulnerable populations dependent on natural resources, where the intensive use of herbicides exacerbates health risks. The general objective of this study is to evaluate the prevalence of metabolic syndrome in the population of the municipality of Belterra. The specific objectives include understanding the sociodemographic profile of the sample, developing the epidemiological profile, and identifying metabolic syndrome using established criteria. The methodology adopts a cross-sectional design with primary data from n = 284 adults residing near agricultural crops, incorporating descriptive analyses of anthropometric, biochemical, and sociodemographic variables. The results indicate a prevalence of 46.1% for metabolic syndrome, higher than urban estimates, with a female predominance of 63.7%, a mean age of 51.31 years, overweight in 41.2% and obesity in 27.5%, in addition to biochemical alterations such as average triglycerides of 170.12 mg/dL. The conclusions highlight the demographic multifactoriality of the condition, proposing interventions such as adapted environmental surveillance to mitigate rural vulnerabilities in the Amazon.